Asset Growth on Sharia Insurance - Warsani Purnama Sari (Britain International for Academic Research (BIAR) Publisher, 2020)
Examining the Premium Income Rate on Asset Growth in a Sharia Insurance Company registered with the Indonesian Financial Services Authority. The type of research used in this study is Comparative Causal, while the sample used in this study are 20 sharia insurance companies with the criteria of sharia insurance companies that are actively operating for the last three years. The results of this study indicate that the level of premium income positively and significantly affect the growth of asset Asuransi Syariah. This study is concerned with the level of premium income that affects the growth of Sharia Insurance assets in Indonesia.